Conservation Notes on Syzygium ampliflorum (Koord. & Valet.) Amshoff and Several Related Species in Java - Kusuma, Yayan Wahyu C. (Proceeding International Conference on Global Resource Conservation, 2013)
Syzygium ampliflorum is listed as Critically Endangered by IUCN red list since 1998. It is an endemic species with a restricted distribution confined to Mount Galunggung, West Java, Indonesia. Revisitation study was conducted by surveying the same area where the species is firstly found and described in 1900. Of the four forest localities as the survey area around the Mount Galunggung there were no detection of the species existence. Meanwhile, eleven other congeneric species (Syzygium racemosum (Blume) DC., Syzygium acutatum (Miq) Amshoff, Syzygium pyrifolium (Blume) DC., Syzygium macromyrtus (K & V) Merril & Perry, Syzygium aemulum (Blume) Koord. & Valeton., Syzygium antisepticum (Blume) Merril & Perry, Syzygium pycnanthum Merril & Perry, Syzygium klampok (Miq.) Amshoff, Syzygium rostratum (Bl.) DC., Syzygium samarangense (Blume) Merril & Perry and Syzygium nervosum DC.) were still found in the study area. Based on the result, there are still some possibilities on the existence of the species. Nevertheless, this species is still enigmatic. Therefore, restate its conservation status as Critically Endangered is more appropriate then include it into Data Deficient. Keywords: endemic, IUCN, ki sireum, reassessment, Redlist, revisitationÂ